CONSERVATION OF WESTERN GHATS: CONTRADISTINCTIVE APPROACHES ADOPTED BY EXPERT COMMITTEES OF MoEF - Ahammed.P AND Jayapal.G
The Western Ghats situated along the west coast of peninsular India, which constitute a unique biological region of the world. It is one of the 25 Global Biodiversity Hot Spots with highest human density and contains more than 30% of all plants and vertebrate species found in India in less than 6% of total geographical area. The degradation of forests is high due to developmental activities such as plantation agriculture, hydroelectric projects, mining, transportation, tourism and conversion of the forest area into residential and commercial use. Ministry of Environment and Forest has appointed Madhav Gadgil as the Chairman of Western Ghat Ecology Expert Panel (WGEEP) to identify Ecologically Sensitive Areas of Western Ghats and to suggest various methods to conserve the biodiversity. The committee submitted the report on August 30, 2011. A strong protest against the report was erupted in Kerala and another committee was appointed under the Chairmanship of Dr. G Kasturirangan as High Level Working Group (HLWG). The Working Group submitted their report on April 15, 2013. As a response, a wide protest had occurred against these two reports due to unfair imposition of strict regulation of those reports. There are wide contradictions in definition, parameters, methodology and extension of western Ghat region. This paper focuses on comparative and critical evaluation of two reports with a view of ground.